Calorimetry of isolated hearts (II) energetic of ca 2+ homeostasis in different animal models and during ischemia – reperfusion - Consolini, Alicia Elvira (2017)
This review describes the application of calorimetry to study cardiac energetics in physiological, pharmacological and pathophysiological conditions of a perfused heart preparation. In particular, the factors influencing the resting heat rate (Hr), such asspecies differences among rat, mouse and guinea-pig hearts, as well as the mechanismsunderlying the increased resting heat rate under a high [K+]-cardioplegia were discussed. Our results give support to a functional interaction between the sarcoplasmic reticulum and mitochondria for myocardial Ca2+ movements. Finally, it is briefly commented the application of calorimetry to study Ca2+ homeostasis during a model of stunning induced by no-flow ischemia and reperfusion in entire hearts by usingselective inhibitors of cellular Ca2+ transporters. Either in the presence or absence ofperfusion, calorimetry allows to evaluate the total muscle economy. As application, calorimetry allows to detect a cardiac dysfunction still under unaltered contractility, demonstrating that it is a very sensitive methodology for studying pathological situations and pharmacological consequences.